Our Lady of Alice Bhatti - Hanif, Mohammed (Alfred A. Knopf, 2012)
The patients of the Sacred Heart Hospital for All Ailments are looking for a miracle, and Alice Bhatti is looking for a job. Alice is a candidate for the position of junior nurse, grade 4. It is only a few weeks since her release from Borstal. She has returned to her childhood home in the French Colony, where her father, recently retired from his position as chief janitor, continues as part-time healer, and full-time headache for the local church. It seems she has inherited some of his gift. With guidance from the working nurse's manual, and some tricks she picked up in prison, Alice brings succour to the thousands of patients littering the hospital's corridors and concrete courtyard. In the process she attracts the attention of a lovesick patient, Teddy Bunt, apprentice to the nefarious 'Gentleman Squad' of the Karachi police. They fall in love; Teddy with sudden violence, Alice with cautious optimism. Their love is unexpected, but the consequences are not. Alice soon finds that her new life is built on foundations as unstable as those of her home. A Catholic snubbed by other Catholics, who are in turn hated by everyone around them, she is also put at risk by her husband, who does two things that no member of the Gentlemen Squad has ever done, fall in love with a working girl, and allow a potentially dangerous suspect to get away. Can Teddy and Alice ever live in peace? Can two people make a life together without destroying the very thing that united them? It seems unlikely, but then Alice Bhatti is no ordinary nurse.